Architectural Changes in the Medial Gastrocnemius on Sonography after Nerve Ablation in Healthy Adults - Park, Jae Eun; Seong, Yeon-Jae; Kim, Eun Sang; Park, Dongho; Lee, Yonghyun; Park, Hyerin; Rha, Dong-wook (Yonsei medical journal, 2019)
Architectural changes in healthy muscle after denervation have not yet been reported. This study aimed to investigate architectural changes in the medial head of the gastrocnemius muscle (GCM) after aesthetic tibial nerve ablation in healthy adults using ultrasonography (US). The effects of tibial nerve ablation were verified by visual observation and surface electromyography analysis. US images of medial GCMs were taken by one trained physician using B-mode and real-time US with a linear-array probe before nerve ablation, at 1 week after nerve ablation and at 3 months after nerve ablation in an anatomic standing position with the feet about shoulder-width apart in 19 healthy adults (17 females and 2 males). Muscle thickness was significantly reduced on the left side at 1 week and 3 months after the procedure and on the right side at 3 months after the procedure ( <0.050). Although fascicle length was not significantly changed, pennation angle was significantly reduced on both sides at 3 months after the procedure ( <0.050). Muscle thickness and pennation angle of the muscle fascicle were significantly reduced, although fascicle length was not significantly changed, after tibial nerve ablation in the medial GCM of healthy adults.